Analysis of Electrical Energy Consumption in the Home Using IoT - Varela-Aldás, José (2022)
The consumption of electrical energy is important in the economy of the home and the internet of things facilitates real-time remote monitoring of electrical parameters. This document performs the analysis of electrical energy consumption in a domestic installation based on the data measured in 2 electrical distribution inputs, this information is collected automatically using a data acquisition device with an internet connection. The electrical monitor used is the Emporia Gen 2 Vue and the information collected is stored for a week in the cloud while the owners rate the activities in the home. To measure the activity level of the home, all 4 household members rate their energy use on a scale of 3 levels. The results show the graphs of electrical energy related to the levels of activity in the home. Surprisingly, the hours of high activity have slightly higher energy measurements than the measurements in the hours of medium activity, but both levels of activity have an observable difference with the hours of low activity. The final analysis allows establishing solutions to reduce the consumption of electrical energy in the home understudy.